Crisis Response Strategy of PT. Angkasa Pura II on the News of Health Protocol Violations at Soekarno-Hatta Airport - Melinda Puspa Negara; Susanne Dida; Retasari Dewi (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2023)
Thursday, May 14th, 2020, the public was shocked by the occurrences of violations of health protocol during the pandemic Covid-19 at Soekarno-Hatta Airport. At that time, the government was relaxing the Large-Scale Social Restrictions (PSBB) by re-activating public transportation modes. Reports in the mass media and social media cornered PT. Angkasa Pura II, the airport administrator, is a party that is negligent in managing flight schedules and rules for maintaining distance at the airport. This research objective was to identify the crisis response strategy carried out by PT Angkasa Pura II to overcome the negative news resulting from the incident of health protocol violations at Soekarno-Hatta Airport. The study discusses crisis response strategies derived from Situational Crisis Communication Theory (SCCT). This research method is qualitative. Research data was obtained through interviews, observation, and literature study. The results of this research, AP II crisis response strategies were, (1) rebuilding, the rebuilding response strategy AP II was conducted with an apology. (2) Take corrective actions, AP II made some physical improvements, increasing field staff and warning signs for applicating health protocols in public spaces. And (3) diminishment, the diminishment response strategy AP II was conducted by submitting excuses and justifications. AP II attempts crisis framing by disseminating information about the company's efforts and commitments that are disseminated through the company's website and social media. This step aims to make the public aware of the company's positive efforts to deal with the crisis and the public also understands that AP II has no intention of committing violations.